Analysis Sex Determination to Forensic Aspect Use Maxillary Sinus Measurement by CBCT: A Pilot Study - Riki Kristanto; Eha Renwi Astuti; Ricardo Henrique Alves da Silva (Budapest International Research and Critics University, 2021)
Analysis sex determination is an important to identification unknown person. CBCT scan can be used to analyzing a dimension in skeletal and for sex estimation when other methods are inconclusive using morphometric aspects, for example through maxillary sinuses can be performed the sex prediction. This study was conducted to estimate the size of the different dimensions of the maxillary sinus to sex determination of an individual by measuring the height, width, length and volume of the maxillary sinus using CBCT in Indonesia. The study of CBCT analysis scan from 20 subject (10 male and 10 female) shows that the potential high score parameter of p value is 0,00 < 0,05 on SI right, MSV right, AP left and MSV Left. It can be used to the prediction of sex determination. Binary logistic regression can be performed 85% from four parameter (SI right, MSV right, AP left and MSV Left) and the result more likely to male. Different result of discriminat function analysis showed the prediction to sex determination use maxillary sinus have percentage 80% to both group. The maxillary sinus measurements are valuable parameters for sex determination in forensic odontology, with a relatively good accuracy rate.